Traumatismo crânio-encefálico: diferenças das vítimas pedestres e ocupantes de veículos a motor Traumatic brain injury: differences among pedestrians and motor vehicle occupants - Regina M. C. de Sousa; Fabiane C. Regis; Maria S. Koizumi (Universidade de São Paulo, 1999)
OBJETIVO: Caracterizar as diferenças das vítimas com diagnóstico de traumatismo crânio-encefálico envolvidas em diferentes condições, em acidentes de trânsito de veículo a motor e evidenciar indicadores para prevenção e seu atendimento. MÉTODO: Foram analisados os prontuários de todas as vítimas com diagnóstico de trauma crânio-encefálico, assistidas em hospital de referência para atendimento do trauma, entre março e junho de 1993. A população foi de 156 vítimas, sendo 80 pedestres, 50 ocupantes de veículos a motor, exceto de moto e, 26 motociclistas ou passageiros de motos. RESULTADOS E CONCLUSÕES: Os resultados mostraram que a mortalidade entre pedestres foi a mais alta entre os três grupos (25,0%). Os óbitos ocorrem em 19,2% dos ocupantes de motocicleta e 8,0% dos ocupantes de demais veículos a motor. Foram observadas diferenças estatísticas entre os grupos quando a variável gravidade do trauma crânio-encefálico foi analisado. Análise de certas variáveis mostraram importantes diferenças na distribuição dos três grupos. OBJECTIVE: The purpose of this study was to discover the differences among victims who had traumatic brain injury due to traffic accidents. METHOD: Medical records of the head injury patients were analyzed according to their classification as traffic accident victims (pedestrian, motorcyclist or passenger and other motor vehicle driver or passenger), age, gender, admission type (admitted from scene of the injury or from another hospital), duration of hospitalization, type of head injury, types of lesions present in other body segments and mortality. Patients injury severity was measured by Injury Severity Score and head injury severity was analyzed using the ranking on the Glasgow Coma Scale, recorded by neurosurgeons during their first neuro assessment. All head injured patients admitted to a trauma center in S. Paulo city over a four-month period from March through June 1993, were included in the study. The sample was of 156 victims, with subsets of 80 pedestrians, 26 occupants of motorcycles and 50 occupants of other motor vehicles. RESULTS AND CONCLUSIONS: The results of this study showed that the mortality rate was higher in the pedestrian subset (25,0%) than among other victims and higher for motorcycle occupants (19,2%) than for motor vehicle victims (8,0%). Statistical differences between the subsets were established when the head injury severity variable was analyzed using the Glasgow Coma Scale. On the other hand, the differences between the three subsets was not statistically significant when the measurement used was the Injury Severity Score. Analyses of other variables showed important differences among subset distributions.